2015
DOI: 10.1111/jam.12993
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Real Fungus-ID kit based on multiplex RT-PCR assay for the rapid detection and identification of Trichophyton spp. and Microsporum spp. in clinical specimens with suspected dermatophyte infection

Abstract: Even though the use of molecular diagnostic technology is more expensive than conventional methods, the clinical and economic benefit of saving time relative to expense remains to be elucidated. Therefore, the multiplex RT-PCR assay may provide the essential information to accelerate therapeutic decisions for earlier and adequate antibiotic treatment in the acute phase of fungal pathogen infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…Moreover, the PCR technique relies on the necessity of using only agarose gel as a detection method of the amplified DNA, which adds to its operational costs (55). A study conducted by Wang et al (56)indicated that physiological differences between individual rDNA repeats exist despite their identical DNA sequence.…”
Section: Molecular-based Candida Detection Methodsmentioning
confidence: 99%
“…Moreover, the PCR technique relies on the necessity of using only agarose gel as a detection method of the amplified DNA, which adds to its operational costs (55). A study conducted by Wang et al (56)indicated that physiological differences between individual rDNA repeats exist despite their identical DNA sequence.…”
Section: Molecular-based Candida Detection Methodsmentioning
confidence: 99%
“…Tratamento das dermatofitoses da população e ao turismo, que proporciona uma maior migração dos microrganismos de sua região de origem para regiões onde antes essas espécies não eram relatadas como causadoras de dermatofitoses. Como resultado da migração, por exemplo, estão sendo relatados casos de infecção por T. violaceum e M. audouinii na Europa e América do Norte, enquanto antes só existiam na Ásia e na África do Sul 31 . Desse modo, o perfil de prevalência das espécies dermatofíticas é bem variado 29 , como se pode observar na Tabela 1.…”
Section: Dermatofitoses Agentes Etiológicos -Fungos Dermatófitosunclassified
“…Corroborando esse fato, a incidência de determinadas espécies é claramente específica a cada região, visto que, no sul do Brasil, M. canis é o principal causador de dermatofitoses, correspondendo a 60% dos agentes etiológicos. Já na região Norte do país, encontramos relatos de T. tonsurans acometendo 74% dos pacientes infectados e M. canis representando a causa do desenvolvimento da micose em apenas uma pequena parcela dos casos 31 .…”
Section: Dermatofitoses Agentes Etiológicos -Fungos Dermatófitosunclassified
“…; Wang et al . ). Accordingly, the common multiplex real‐time RT‐PCR method was developed for plant material that was infected with multiple viruses, for example, the potato with the Potato mop top virus (PMTV) and the Tobacco rattle virus (TRV) (Mumford et al .…”
Section: Introductionmentioning
confidence: 97%